The extent of knowledge abd compliance with the copyright law of the librarians of the Department of Justice and its attached agencies - Santos , Marilou M.; Aguirre, Vyva Victoria M.; Santos, Antonio M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2008)
Law librarians deal mainly with legal information and materials and it is important that they are aware of the law affecting libraries and librarians, like the copyright law. This study exemplifies the librarians of the Department of Justice (DOJ) and its attached agencies having operational libraries, on the extent of their knowledge and compliance with the copyright law, focusing on their reprographic reproduction practices. The study aims to determine the librarians' extent of knowledge and compliance with the copyright law, and to describe the reproduction practices and specific institutional cases concerning copyright-related policies.
As the study's respondents, the twelve (12) professional librarians of the DOJ and its attached agencies were surveyed using a questionnaire to test on specific copyright provisions and to ascertain their respective institution's compliance efforts.
The results of the study revealed that the respondents were moderately knowledgeable about the legal provisions and can be said to be within reasonable limits. As to their compliance efforts and reproduction practices, it was found out that despite the absence of copyright-related policies in place, the respondents were also conscious of the limitations concerning reproduction of materials because majority of them reproduce mostly specific pieces of laws and cases for in-house compilations and to serve the individual interests and needs of their own constituents.
Specific institutional cases seen through the individual perspectives of the respondents pointed to the need to know the law itself and the violations under the law, specifically on the aspect of photocopying. Accordingly, these also constituted the supposed contents of a copyright policy should they make one. In addition, most of them considered to participation in seminars and self-study, as the means to learn about the law. Interestingly, it was noted that almost half of the respondents have not attended any copyright-related organized activities, while the others attended only once or twice.
The relevance of the copyright law was duly recognized by the majority of the respondents, rating it as Very Relevant to libraries. This means that they still give much important to it in relation to their work. A few of the respondents cited non-relevance of the law as far as their library situations are concerned. This may be objectively interpreted as having reference to the inappropriateness of the law to their own purposes, inasmuch as they gave the justification that their institution purchase their own informational requirements and not depend on reproduction of required materials.
Having indicated that the respondents were within reasonable limits as to their knowledge of the law and their compliance thereof, the study further recommended that the subject libraries formulate copyright policies in unison with the Code of Ethics for Librarians; popularize the topic in library schools' curricula; conduct more functional seminars and for library organizations to facilitate active educational campaign drives, among others.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Law librairans -- Philippines; Copyright